Eburnean deformation pattern of Burkina Faso and the tectonic significance of shear zones in the West African craton - (:unkn) unknown (My University, 2020)
Shear zones of the Paleoproterozoic Eburnean accretionary Orogen (West African craton) are investigated by means of large-scale structural mapping. Regional scale (10-100 km) mapping was based on the aeromagnetic survey of Burkina Faso and craton-scale (1000 km) mapping on a compilation of fabric data. At both scales, shear zones are arranged as an anastomosed transpressional network that accommodated distributed shortening and lateral flow of the orogenic lithosphere between the converging Kénéma-Man and Congo Archean provinces. Structural interference patterns at both scales were due to three-dimensional partitioning of progressive transpressional deformation and interactions among shear zones that absorbed heterogeneities in the regional flow patterns while maintaining the connectivity of the shear zone network. Such orogen-scale kinematic patterns call for caution in using the deformation phase approach without considering the “bigger structural picture” and interpreting displacement history of individual shear zones in terms of plate kinematics. The West African shear zone pattern is linked to that of the Guiana shield through a new transatlantic correlation to produce an integrated kinematic model of the Eburnean-Transamazonian orogen.
Keywords: African Research